(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2026)
Himachal Pradesh, renowned for its pristine natural landscapes and tranquil environment, has witnessed rapid urbanization and increased human activities in recent years. This shift has sparked concerns regarding the potential impacts of noise pollution on the environment and public health. The objective of this study was to thoroughly evaluate the soundscape and map noise pollution levels across various regions of Himachal Pradesh. Employing a mixed-methods approach, the research has combined acoustic measurements, Geographic Information System (GIS) technology, and community surveys. Sound level measurements have been gathered at strategic points across urban, sub-urban, and rural areas of the state, capturing both ambient noise and specific events. Geographic data have been integrated to construct noise pollution maps, providing spatial insights into noise distribution and identifying hotspots. Additionally, community perception surveys was conducted to assess the impact of noise pollution on residents’ well-being and quality of life. This research paper will contribute to the knowledge base by providing valuable insights into the current soundscape of the state and laying the groundwork for sound urban planning and noise management strategies. The findings have suggested for preserving the tranquillity of Himachal Pradesh’s natural environment while safeguarding the well-being of its residents amidst growing urbanization and development pressures.